PENGARUH PENDEKATAN PEMBELAJARAN DAN PENGUASAAN SEMANTIK TERHADAP PENINGKATAN PEMAHAMAN MAKNA PUISI - Djojosuroto, Kinayati (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2014)
The article presents in this research findings is intended to determine the influence of teaching approach and semantic mastery on the increase of students' achievement of poetry comprehension of the students of the Education of Language and Literature program of the Language and Art Major of the Manado State University (UNIMA). The teaching approach as an independent variable is divided into three levels: Gestalt, Structural, and Semiotic. The semantic mastery as an attribute variable is divided into high semantic mastery and low semantic mastery. The research method employed in this study was quasi-experiment with before-after design through the factorial of 3 x 2 of the two-way analysis of ariance technique (ANAVA). The sample of this research was the students who were studying the poem appreciation subject. Based on the result of inferential analysis of the data, several conclusions may be drawn. First, there is a difference in the increase of achievements of poetry comprehension of the groups of students who are taught using Gestalt approach, structural approach, and semiotic approach (p 0.05). Among the three groups, the Gestalt group shows the highest increase. Second, the group of students with high semantic mastery shows a higher increase of achievement in poetry comprehension than those with low semantic mastery (p 0.05). Third, there is an interaction between teaching approach and semantic mastery in terms of the increase of the students' achievement (p 0.05).